A Brief Account of Iterative Big Data Clustering Algorithms - Shankar Lingam, M; Sudhakara, AM (International Journal of Computer Sciences and Engineering, 2025)
Today, maximum of the organizations have to deal with big quantities of records, that is hastily growing. In order to address these explosively growing amounts of information, one has so that it will extract, examine, and process information time to time. Clustering has for this reason been identified keeping in view this example and it is considered as an essential device used to analyze huge statistics. Technological progress, specifically inside the regions of finance and enterprise informatics, poses a big task for big scale records clustering. To deal with this issue, researchers have provided you with parallel clustering algorithms that are primarily based on parallel programming fashions. MapReduce is one of the most typically used frameworks used for this motive and it has received high consciousness thanks to its flexibility, fault tolerance and programming ease. However, the overall performance has trouble for iterative packages. This paper gives an in depth evaluation of iterative frameworks which could help MapReduce for overcoming boundaries for iterative algorithms.